Feasibility of exercise therapy for children with asthma: a meta-analysis - Zhou, Linyuan; Xu, Haofu (Frontiers in Cell and Developmental Biology, 2023)
Background: Although numerous studies have demonstrated the clear benefits of exercise for people with asthma, controversy remains. This study evaluated the effects of sustained exercise types on lung function and quality of life in patients with asthma. Methods: We searched PubMed, EMBASE, Web of Science, Cochrane Library, China National Knowledge Infrastructure (CNKI), and Wanfang database since January 2000 to August 2022 .included randomized controlled trials (RCTs) of asthmatic children intervened with exercise. The outcomes were lung function and asthma-related quality of life. Fixed-effects model (I2≤50%) or random-effects model (I2>50%) was applied to calculate the pooled effects. Funnel plots were quantified to present publication bias, and a P value <0.05 was statistically significant. Results: Eventually, 15 trials conformed to the selection criteria. The exercise group significantly improved lung function (FEV1 and FVC) in asthmatic children compared with the control group. Forced Expiratory Volume in 1 Second (MD = 2.12, 95%CI = 0.70, 3.53; p = 0.003; I2 = 15%); Forced Vital Capacity (MD = 2.78, 95%CI = 1.26, 4.31; p = 0.0004; I2 = 56%). The immune system markers IL-6 and TNF-α, were significantly reduced in the exercise group. Interleukin-6 (MD = −0.49, 95%CI = −0.81, −0.17; p = 0.003; I2=0%); tumor necrosis factor-α (MD = −0.54, 95%CI = −0.92, −0.15; p = 0.006; I2 = 0%). That quality of life (PAQLQ) was significantly improved in children with asthma in the exercise group. PAQLQ-Total score (MD = 1.06, 95%CI = 0.46, 1.66; p = 0.006; I2 = 94%); PAQLQ-Emotional (MD = 0.91, 95%CI = 0.76, 1.06; p<0.00001; I2 = 90%); PAQLQ-symptoms (MD = 0.87, 95%CI = 0.71, 1.02; p<0.00001; I2 = 95%); PAQLQ-activities (MD = 1.20, 95%CI = 0.58, 1.82; p = 0.00001; I2 = 93%). Meta-analysis showed significant improvements in body composition in the exercise group. BMI (MD = −2.42, 95%CI = −4.40, 0.44; p = 0.02; I2 = 85%). Conclusions: This meta-analysis demonstrated the effectiveness of exercise in improving pulmonary function index (FEV1, FVC), immune system (IL-6, TNF-α, Feno), exercise ability (6MWT), body composition (BMI), and quality of life (PAQLQ) in asthmatic children. Asthmatic children should regularly participate in physical exercise.